2020
DOI: 10.1063/5.0015346
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the radio frequency sheath of plasma with Cairns–Tsallis electron velocity distribution

Abstract: The effect of the non-Maxwellian plasma with enhanced electron tails on the properties of the radio frequency (RF) sheath is studied with a one-dimensional collisionless model, which consists of the sheath model and the equivalent circuit model. In the sheath model, electrons are assumed to obey the Cairns–Tsallis distribution. For various entropic indices q characterizing the degree of electron nonextensivity and parameter α measuring the electron nonthermality state, the electron nonextensivity and nontherma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The following typical parameters at EAST-like tokamak during ICRF wave heating are used in this paper [21]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following typical parameters at EAST-like tokamak during ICRF wave heating are used in this paper [21]:…”
Section: Resultsmentioning
confidence: 99%
“…The change of the sheath structure caused by supra-thermal electrons can affect the dynamics and charging process of the dust grains in the sheath, current-voltage characteristics, ion bombardment energy and plasma energy flux to the wall. In an unmagnetized RF sheath, it is shown that the supra-thermal electrons can enhance the sheath potential drop at any time [9,20,21]and the resultant effect of the IED [9]. In some plasma fields such as laboratory and fusion plasmas, the magnetized RF sheath with non-Maxwellian electrons may be formed, and the shape of the IED depends very likely on both the magnetic field and supra-thermal electrons because it has been confirmed from the static sheath that the sheath structure can be modified by the interplay of the supra-thermal particles and magnetic field [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…[35] From 2012 to 2020, various studies have been presented by using this hybrid distribution for linear and non-linear plasmas given in the Refs. [36][37][38][39][40][41][42][43][44][45] Recently, IAWs have been studied in Vasyliunas-Cairns distributed plasmas with two non-thermal parameters (𝜅, 𝛼). [46] The purpose of this paper is to explore the unique features of IAWs by using the kinetic theory approach in non-thermal hybrid plasmas with Cairns-Tsallis distributed (CTD) electrons.…”
Section: Introductionmentioning
confidence: 99%
“…(1995) also introduced a nonthermal distribution function to model the populations of nonthermal or energetic electrons observed in space plasmas by Freja and Viking satellites (Bostrom, 1992; Dovner et al., 1994). There are a lot of theoretical considerations of nonthermalities in plasmas (Abid et al., 2016; Darian et al., 2019; El‐Taibany et al., 2018, 2019; Farooq et al., 2018; Guo & Mei, 2014; Ou & Men, 2020; Rajib et al., 2019). The presence of nonthermal populations of particles has also been investigated in the plasmas produced due to laser‐matter interaction (Futaana et al., 2003; Sarri et al., 2010).…”
Section: Introductionmentioning
confidence: 99%